Efficacy and Safety of Early Use of Naoxueshu Within 72 hours in the Treatment of Spontaneous Intracerebral Hemorrhage: A Real-World Retrospective Cohort Study - Wang X; Shang Z; Zhao J; Hou H; Li Y; Song J (International Journal of General Medicine)
Xinyu Wang,1,* Zhiyuan Shang,2,* Jiapeng Zhao,1,* Hongping Hou,3 Ye Li,4 Juexian Song1 1Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Neurosurgery, Beijing Fengtai You’anmen Hospital, Beijing, People’s Republic of China; 3Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 4Department of Neurosurgery, Xuanwu Hospital, Capital Medical University, National Center for Neurological Disorders, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ye Li; Juexian Song, Email yli@xwhosp.org; songjuexian@vip.163.comBackground: Naoxueshu Oral Liquid (NXS) is the only traditional Chinese medicine approved for the treatment of spontaneous intracerebral hemorrhage (ICH). While randomized controlled trials have demonstrated its ability to promote hematoma absorption and improve neurological function prognosis, the efficacy and safety of NXS early use (within 72 hours) remain unclear. This study aims to evaluate the efficacy and safety of early NXS administration (within 72 hours) in a real-world setting.Methods: Data were collected from 34 tertiary hospitals in China. Patients were enrolled from March 25, 2019 to December 31, 2023. NXS administration was defined as the exposure. The primary outcome was hematoma volume at 14 days after onset. We employed the 1:1 propensity score matching (PSM) method to deal with confounding factors.Results: A total of 1602 patients were enrolled after PSM, including 872 NXS users (exposed group) and 730 non-NXS users (control group). At baseline, there was no significant difference in hematoma volumes between the two groups (21.46± 19.47 vs 22.01± 14.26mL, P=0.55), the NXS group showed significantly less hematoma volume by day 14 (6.87± 8.62 vs 5.43± 5.35mL, P< 0.001). There was no statistically significant difference in the incidence rate of serious adverse events between the two groups. Subgroup analysis indicated that NXS might have a more pronounced effect on hematoma absorption in supratentorial hemorrhage patients, with earlier administration potentially enhancing efficacy.Conclusion: This retrospective study explored the efficacy and safety of NXS in promoting hematoma absorption within 72 hours in real-world ICH patients, but its effect on short-term neurological improvement remains inconclusive. Further studies with longer follow-up periods and more comprehensive functional assessments are warranted to explore the long-term neurological benefits of NXS in ICH patients.Keywords: intracerebral hemorrhage, traditional Chinese medicine, real-world